Nanoscale subcellular architecture revealed by multicolor three-dimensional salvaged fluorescence imaging - Zhang, Yongdeng; Schroeder, Lena K.; Lessard, Mark D.; Kidd, Phylicia; Chung, Jeeyun; Song, Yuanbin; Benedetti, Lorena; Li, Yiming; Ries, Jonas; Grimm, Jonathan B.; Lavis, Luke D.; De Camilli, Pietro; et al. (Nature methods, 2020)
Combining the molecular specificity of fluorescent probes with three-dimensional imaging at nanoscale resolution is critical for investigating the spatial organization and interactions of cellular organelles and protein complexes. We present a 4Pi single-molecule switching super-resolution microscope that enables ratiometric multicolor imaging of mammalian cells at 5–10-nm localization precision in three dimensions using ‘salvaged fluorescence’. Imaging two or three fluorophores simultaneously, we show fluorescence images that resolve the highly convoluted Golgi apparatus and the close contacts between the endoplasmic reticulum and the plasma membrane, structures that have traditionally been the imaging realm of electron microscopy. The salvaged fluorescence approach is equally applicable in most single-objective microscopes. 4Pi single-molecule switching microscopy combined with ‘salvaged fluorescence’ enables improved ratiometric imaging that bypasses chromatic aberrations and allows for multicolor whole-cell imaging with sub-10-nm localization precision.